MANAGEMENT OF CASH WAQF AT BSI MASLAHAT REGION 8 SURABAYA FOR 2022 – 2024 IN ACHIEVING THE SDGs - Faris Khoirudin; Dian Berkah; Rukhul Amin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the productive waqf management system at BSI Maslahat Surabaya as a nazhir institution in collaboration with Bank Syariah Indonesia (BSI). This research uses a qualitative method, with a case study approach that includes interviews, documentation and drawing conclusions. The results of the study show that BSI Maslahat Surabaya has successfully implemented a transparent waqf model with BSI in the management of productive waqf. This collaboration allows the optimization of the collection, management, and distribution of waqf funds professionally through the Integrated Fund Management System (IFMS). BSI Maslahat Surabaya manages two forms of waqf, namely money waqf and waqf through money, the proceeds of which are distributed to social programs such as Al-Qur'an Grants, Waqf for the construction of BSI Mosque in Bromo, BSI Qur'an House in Magetan. The application of Sharia Good Governance principles makes this institution credible and accountable. Overall, BSI Maslahat Surabaya is a model for modern productive waqf management that is sustainable and has the potential to strengthen the sharia economic ecosystem in Indonesia.